CLIMATE CHANGE , LAND DEGRADATION , AND DESERTIFICATION IN THE MEDITERRANEAN ENVIRONMENT - Wrachien, D De; Ragab, R (Desertification in the Mediterranean Region a Security Issue)
Until the early seventies land degradation and desertification were not considered a major issue in most Mediterranean regions. Traditional agricultural systems were believed to be able to keep those processes in check. Thus low priority was assigned to research programmes and projects on soil erosion and conservation, preference being given to the impact of farm machinery on soil structure and compaction along with the role of organic matter in the soil. In the eighties and early nineties the agricultural practices introduced in sloping land under cultivation in the Mediterranean in previous decades were identified as a major contributor to soil degradation. The unprecedented efforts to increase crop yields and maximize profit, made possible by the technological revolution in agriculture, had triggered in the agricultural ecosystem the onset of soil degradation due to hydrological phenomena that proved detrimental both to soil fertility and to the landscape causing devastating and permanent damage. In addition, it was recognized that research activities were too fragmentary to be able to cope with the demands of implementing sound soil conservation measures. The Mediterranean climate is characterised by hot dry summers and mild wet winters. The region frequently suffers from years of scant rainfall and many areas are afflicted by severe drought. The UK Hadley Centre's global climate model has been run on a monthly basis for the Mediterranean countries to predict the percent variation in rainfall and temperature with respect to mean monthly values. Scenarios developed using the model show that for the wet season (October-March), by the year 2050 rainfall could increase in central and eastern Spain, northern France, northern Italy and the Alps by up to 15%, against a decrease of about 10% to 15% in the southern Mediterranean. For the same period, the temperature in the northern Mediterranean is predicted to increase by 1.25° to 2.25°C, compared to an increase of between 1.5° and 2.5°C in the southern Mediterranean. The projections also show that for the dry season (April to September), by the year 2050 rainfall is likely to decrease over much of the Basin. Decreased precipitation is predicted to be accompanied by a rise in temperature of between 1.5 and 2.75°C in the northern regions and 1.75° and 3.0°C in the southern Mediterranean. Reduced precipitation during the summer has a major impact on irrigation and tourism, which both increase the pressure on water supplies during the dry period. To combat these problems, the European Community (EC), in collaboration with other international organizations, has funded various programmes and projects for mitigating drought and assessing and preventing land degradation and desertification. In this context, the paper describes the main features and characteristics of some of these programmes and projects and proposes new approaches to environmental policies, in order to: • • • • • assess, forecast and mitigate adverse impacts of drought; better understand soil erosion, land degradation and desertification processes; identify preventive, protective and remedial measures; address quantity and quality of natural resources in an integrated context; support innovation and participatory strategies. The importance and role of institutional strengthening, sound financial and managerial frameworks, availability of human resources involved, research thrust, technology transfer and networking improvement are also highlighted.
Keywords: climate change; EU programs; land degradation and desertification

DESERTIFICATION AND ENVIRONMENTAL SECURITY . THE CASE OF CONFLICTS BETWEEN FARMERS AND HERDERS IN THE ARID ENVIRONMENTS OF THE SAHEL - Herrero, Sergio Tirado (Desertification in the Mediterranean Region a Security Issue)
Traditional production systems in the Sahel are based on the integration of activities sharing and competing for renewable resources (water and soil fertility) under threat of desertification. A framework of relationships ranking from conflict to collaboration between human groups devoted to agriculture and pastoralism has been developed throughout history and has proven to be successful in sustaining the livelihood of the region’s population. Changes in the economic, social and political structure of the Sahel related to the process of colonization and de-colonization substantially altered the way in which resource scarcity was dealt previously. In a context of widespread social tension and political instability, this is thought to have increased the likelihood of farmers-herders conflicts. In this paper, we explore the worsening security conditions of the rural Sahel in the light of the new environmental security theories, which help to widen the focus of conflict analysis bringing in social, political, economical and environmental issues that were formerly disregarded
Keywords: conflict and collaboration; desertification; environmental security; farmers and herders; sahel; scarcity

THE USE OF ALTERNATIVE FUTURES IN A STRATEGY TO ASSESS THE LIKELIHOOD OF LAND DEGRADATION LEADING TO INCREASED SUBSEQUENT POLITICAL INSTABILITY - Mouat, David A; Bassett, Scott; Lancaster, Judith (Desertification in the Mediterranean Region a Security Issue)
As stated by the United Nations Convention to Combat Desertification (UNCCD), desertification or land degradation is at the root of political and socio-economic problems and poses a threat to the environmental equilibrium in affected regions. That desertification and political instability are interlinked should not be a surprise, the UN states that half of the 50 armed conflicts in 1994 had environmental causal factors characteristic of drylands (i.e., land degradation). One example cited states that the land’s loss of productivity exacerbates poverty in the drylands, forcing its farmers to seek a way of living in more fertile land or cities. In fact, over one billion people are affected as a direct consequence of desertification including 135 million people who are at risk of being displaced. The physical, biological and social causes of desertification that lead to grave human impacts are interlinked with significant feedback mechanisms. Soil salinization, for example, may result from unsuitable irrigation practices. Changes of vegetation from perennial grasses to shrubs and to annual grasses and forbs might result from overgrazing. Increases in poverty and human out-migration might result from declining agricultural productivity caused by salinization and overgrazing. Because poverty forces the people who depend on land for their livelihood to overexploit the land for food, energy, housing and source of income, desertification can be seen as both the cause and consequence of poverty. Any effective mitigation strategy must address poverty at its very center. It must take into account the social structures and land ownership as well as pay proper attention to education, training and communications in order to provide the fully integrated approach which alone can effectively combat desertification. Seeking solutions to such complex problems requires appropriate technologies and common sense. This paper suggests a technique, alternative futures analysis, to model the likelihood of future land uses in a given region undergoing desertification or at great risk to desertification and to develop an understanding of the risk to political instability coming from each of the alternatives. Furthermore, alternative futures analysis provides a technique (and communication strategy) for illustrating possible conflicts as well their causes and potential solutions. Such a strategy would help local, national and regional land managers, working with their constituent stakeholders to mitigate such effects. A framework for a pilot project employing this technique is presented.
Keywords: alternative futures analysis; desertification; Land degradation; land use; security risk (voyant); social stability

DESERTIFICATION–A NEW SECURITY CHALLENGE FOR THE MEDITERRANEAN? Policy agenda for recognising and coping with fatal outcomes of global - Brauch, H G (Desertification in the Mediterranean Region. A Security …, 2006)
Desertification (representing soil degradation) is one of the three nature-induced (climate change, hydrological cycle) and of three primarily human-induced challenges (population growth, urbanisation and food) of global environmental change. These six components closely interact and contribute to fatal outcomes: primarily to extreme weather events and hydro-meteorological disasters (drought, flash floods, storms) and environmentally-induced migrations. These two fatal outcomes may have – in some cases – societal repercussions that may trigger or contribute to domestic, regional and international crisis and conflicts and thus they may become an issue of both human, societal, national and international security. To illustrate the causal linkages: for example in Morocco in the 1980s and 1990s, the following chain of events could be observed: severe drought, increase in food prices, hunger riots, general strikes, the police and armed forces interfered to repress these violent upheavals and subsequently hundreds of casualties could be deplored. These cases were not listed as a conflict in the relevant conflict data bases. The paper is organised in three parts: In the first part, the complex casual interactions among six factors of global environment change, two fatal outcomes and three societal repercussions: crises, conflicts and conflict avoidance, prevention and resolution will be discussed. In the second part, different security concepts will be reviewed that may be of relevance for dealing with desertification as a security issue. In the third part, possible security relevance pro-active political strategies will be considered, to avoid, and prevent that desertification issues can pose security challenges, and to contribute to a resolution of the desertification driven violence. 11
Keywords: conflict; desertification; Drought; environmental degradation; environmental security; food security; Global change; human security; Land degradation; migration; natural disasters (voyant)

DRYLAND DEVELOPMENT , DESERTIFICATION AND SECURITY IN THE MEDITERRANEAN - Safriel, Uriel N (Desertification in the Mediterranean Region a Security Issue, 2006)
Bioclimatically, The Mediterranean basin comprises a transition between southern desert (Saharian-Arabian deserts) and northern non-desert (European woodlands). Using UNEP´s aridity classification, the political boundaries of all Mediterranean countries include the whole range of dryland types: from south to north, southern Mediterranean countries which are closer to the Sahara-Arabian deserts than the northern Mediterranean countries, have hyper-arid drylands (true deserts), semi-arid drylands, and dry-subhumid drylands; north Mediterranean countries have semi-arid drylands, dry subhumids drylands, and non- drylands regions – humid areas. The UNCCD does not regard hyper-arid drylands as prone to desertification, hence all Mediterranean countries have within their boundaries areas prone to desertification and areas not prone to desertification; in southern Mediterranean countries not prone to desertification are the southern-most and driest regions, and in the northern Mediterranean countries – these are the northern-most and driest region, and in the northern Mediterranean countries – these are the northern-most and least dry regions. The eastern Mediterranean countries – Israel, Lebanon and Syria combined, present the full south- northen gradients of the global drylands. The southernmost of the three, Israel comprises all four dryland types within its boundaries with more than half of its territory prone to desertification, and the analysis of its development, desertification and security can serve as a case study with lessons to the Mediterranean region as a whole. From the dawn history the country has been under intensive land use by humans, including pastoralism and cropping. The new Israel viewed its semi-arid areas, most prone to desertification, as a security risk, and set out to settle them mainly through agricultural development, extensive afforestation projects, rehabilitation of vegetation and restoration of water-related ecosystem services. Exploitation and grazing pressure on the dry subhumid scrublands have been reduced, with fast transition of the vegetation to woodland formation, with restoration of water and soil related ecosystem services. The sustainability if this agricultural development and its potential to avert salinization were driven by transportation of high-quality irrigation water from dry subhumid-generated resources to drier regions. This has been augmented by water conservation hinged on drip irrigation, and by research and extension services. Dry subhumid areas, arid and hyperarid areas have benefited from the agricultural experience gained in the semi-arid region and the infrastructure established to supor tit. Afforestation practices developed for the dry subhumid areas have “migrated” to semi-arid and arid regions. The discovery of geothermal, brackish fossil groundwater and the adaptation of greenhouses to growth houses in dry and hot regions provided farmers with options of intensive cash-crop agriculture and aquaculture – practices that are economic on land use and hence of little if any desertification impact. During its first decades, Israel rehabilitated many previously desertified areas and prevented further desertification. But in recent decades desertification has reemerged. In the dry subhumid areas there is soil salinization, and increasing impenetrability of dry sughumid woodland and “bush encroachment” leading to degraded range quality and woodland fires leading to soil erosion. In the semi-arid areas there is soil erosion of irrigated fields and intensified gully erosion in croplands and rangelands. Salinization of a large scale is expected due to expanding areas of agriculture irrigated with non-desalinated treated wastewater. Thus, rather than generating security problems due to desertification, the attempt to avert security problems by intensified development, eventually lead to desertification.
Keywords: aridity index; biological productivity; desertification; development; drylands; mediterranean countries; Security (voyant); Soil moisture; vulnerability; water use effciency

IMPACT OF FOREST FIRES ON HYDROLOGICAL PROPERTIES OF A TYPICAL MEDITERRANEAN FOREST SOIL - González, O; Andreu, V; Rubio, J L (Desertification in the Mediterranean Region a Security Issue, 2006)
Fire is one of the most important determining factors in the evolution of Mediterranean ecosystems. Its effects on soil are plural and diverse, acting on structure, chemical and physical properties, biota etc. Among them, the induced variations on soil water dynamics are of key importance for the recovery of the entire ecosystem and in the soil response to erosion processes. Forest fires are also a factor, triggering the risk of desertification. The aim of this study is to assess the impact effect of different fire intensities on soil hydrology and on runoff generation. This work was developed in the Permanent Experimental Field Station of La Concordia with nine plots (4 x 20 m), installed in a calcareous hillside, representative of Mediterranean shrubland areas. Experimental fires, of two intensity levels were carried out. Three plots were burned reaching high fire intensity and three other plots were burned with moderate intensity and the remaining plots were left undisturbed as control. Soil water content, water retention capacity and pF curves were measured together with runoff generation dynamics, in the different plots. The intrinsic characteristics of each rain event occurred up until a year after the fires and runoff generated on them was monitored. The data obtained was compared with the state of the plots after seven years, during the 2000-2002 period. In this period 24 rain events with runoff generation occurred, with average rainfall intensities (I30) around 10mm h-1. Both fire treatments show significant differences with respect to the Control plots, which are reflected in a value of runoff production of 76.84% as an average, less than the burned plots. Between fire treatments, the plots that burned with high intensity, show the highest values of runoff yield. However, infiltration rates do not give significant differences between fire treatments. In the same way, plots that suffer a high intensity fire show greater values (22.50 cm3 cm-3) on water retention capacity than the other treatments, giving significant differences with the Moderate intensity plots and Control plots. Differences on this parameter between plots burned with Moderate intensity and the Control plots were observed but they were not statistically significant. The obtained pF curves show the same tendencies, being the greatest water content retained at pF of 2 in the burned plots and in the Control plots at pF of 4.2. The effect of fire degrading the vegetation cover and by means of the temperature impact on soil, produce changes in its structural characteristics and porosity, affecting soil water distribution and the effective response on water erosion processes.
Keywords: desertification; experimental fire; hydrology; Mediterranean; pF curve; water retention capacity

MIGRATION : AN IRREVERSIBLE IMPACT OF LAND DEGRADATION IN TURKEY - Kapur, S; Akça, E; Kapur, B; Öztürk, A (Desertification in the Mediterranean Region a Security Issue, 2006)
The total arable land in Turkey is 28.054.000 ha. However, the prime soils cover only 17.5% of the total land surface and the productivity of the remaining soils is mainly limited by topography, depleted organic matter and high clay contents. The long standing deforestation, unsuitable tillage and irrigation management have induced the rate of erosion since historical periods. The majority of the country’s soil (76.5%) are prone to erosion risk due to the dominant steep slopes (>6%), and 72% of the soils are more or less affected from water and wind erosion (CCD-Turkey, 2003). Soil sealing and extraction of raw material together with overuse of fertilizers and irrigation have led to the improper use of traditional environmental friendly agroscape (agroecosystem), thus constantly degrading the soils of the country. Secondary salinity builds up in the primary saline zones as well as the fertile alluvial planes of Turkey, which are actually the gene zones of many crops particularly cereals, legumes and halophytes, pointing out to the reality that irrigation management plans should not only be based on the concept of conventional cash crop production but also for the crop present on the indigenous agroescapes. This necessitates the incorporation of the halophyte production in the central Anatolian steppes and the olive/carod/vine production in the semi-arid Mediterranean karstic region together with the south east Anatolians calcrete agroscapes. This paradigm is sustainable land use management aims to increase the welfare of the urban people and decrease the threat of excess water use in fragile steppe, karstic and calcrete topographies, which are also the carbon pools of the world. Hence, the concept of agroscapes based on landuse assessment should primarily be considered in the development of sustainable land management strategies particularly with the incorporation of indigenous environmental friendly technical knowledge to combat land degradation and desertification. The high population increase in the urban regions and conversely the decrease in the rural, cause the intensive use of arable land around the former inducing desertification. According to the census of 2000, 40%of the country’s population live in rural area (23.797.653 out of the total 67.803.927) with an average of 1.21 ha/man arable land, mostly allocated for cereal production (country average ~2000Kg/ha.). This is equivalent to a low net income rate, which results to migration from the rural areas to urban, particularly from the east of the country to the west. The Government Statistics Institute (2003)date reveals that from 1990 to 2000, the urban population increased by 30%, ie from 33.656.275 to 44.006.274, whereas the rural increased at much lower rate (4.3%). This data reveals the pressure of both natural and human induced factors on soils and land urgently in need of sustainable land management policies along the legislations, since, the rate of quality loss of land and soil, ie desertification in the coming decades will ultimately be the common jeopardy in the country.
Keywords: Land degradation; land management; Migration (voyant); Soil sealing; Turkey

PART . VI Desertification Indicators and Forecasting Techniques ENVIRONMENTALLY SENSITIVE AREAS AND INDICATORS OF DESERTIFICATION - Kosmas, C; Tsara, M; Moustakas, N; Kosma, D; Yassoglou, N (Desertification in the Mediterranean Region a Security Issue, 2006)
Desertification is the consequence of a series of important processes in the Mediterranean environments, especially in semi-arid and arid regions, where water is the main limiting factor of land use performance on ecosystems. Among the most important processes of desertification are soil erosion and salinization particularly affecting hilly areas and lowlands, respectively. Various methodologies have been developed in identifying and mapping environmentally sensitive areas (ESAs) to desertification. Studies have shown that the various types of ESAs have different behavior on crop production, plant growth, grazing capacity, and soil erosion rates. For example, olive oil and cereal production decreased as the type of ESA changes from non-threatened to critical areas. Soil erosion measures have shown that soil erosion rates increased as the sensitivity of land to desertification increased. Loss in land productivity greatly affects farmer’s income and measures applied for protecting the land from further degradation and desertification. The necessity of elaborating indicators is one of the priorities identified by the United Nations Convention to Combat Desertification (UNCCD). The use of indicators can generally simplify complex processes and provide appropriate tools for combating desertification. Indicators can be classified to those related a) to the physical environment (soil, vegetation, climate), b) to the land management (tillage operations, irrigation practices, animal density grazing the land, forest fire protection, erosion measures, etc), and c) to the socio-economic characteristics (farmer age, family size, farm size, subsidies, farmer income, etc). Indicators can be better used for defining land desertification risk if they are classified according to the land use type. For example important indicators for defining desertification risk for vineyards are related to land management as well as to land characteristics such as tillage operations, tillage direction, slope gradient, parent material, plant cover, etc. Studies, conducted in areas in which the main process of desertification was salinization, showed that important indicators for defining desertification risk were ground water depth, drainage, water quality, frequency of flooding, distance from the seashore, type of land use, rainfall, etc.
Keywords: desertification indicators; land management; land use type; soil erosion; water quality (voyant)

Restoration of burned areas in forest management plans - Alloza, J A; Vallejo, R (Desertification in the Mediterranean Region. A …, 2006)
Wildland fire is a major disturbance promoting landscape changes and triggering desertification processes in the Northern Mediterranean basin. Addressing that issue in the long term requires both fire prevention and pot-fire restoration measures. Post-fire restoration should mitigate ecosystem degradation, and improve ecosystem regeneration rate and quality. The impact of wildfires is especially acute in the transition between semi-arid and dry subhumid climates, where dry vegetation fuels facilitate fire spread and water shortage limits post-fire regeneration. In addition, the occurrence of torrential rains produces a high risk of post-fire flash-floods, especially in autumn after summer fires. The major objectives of post-fire restoration are soil and water conservation and increasing ecosystem resistance and resilience in front of fire. Post-fire restoration strategies are defined according to the degradation stage of the ecosystems and the recovery capacity of vegetation. Plant cover regeneration rate highly influence post-fire soil erosion and flooding risk. The abundance of woody resprouters is recognized in eastern Spain as a critical factor to ensure an efficient recovery of plant cover after fire. Post-fire restoration planning is addressed taking into account vegetation fragility to wildfires, together with soil erosion risk and soil moisture availability (physical features). Vegetation fragility is defined both in relation to spontaneous regeneration capacity of plant cover and in relation to the ability of keystone woody species topersist after fire. A synthetic indicator to asses wildland protection and restoration priorities in relation to wildland fires is developed by combining vegetation fragility and physical layers in a GIS. William G. Kepner, Jose L. Rubio, David A. Mouat & Fausto Pedrazzini, eds. Desertification in the Mediterranean Region a Security Issue, : 475 © 2006 Springer. Printed in the Netherlands. 475–488.
Keywords: degradation (voyant); desertification; erosion; fire; FOREST; Mediterranean; Regeneration; Restoration; Soil

USING A GIS FOR SUSTAINABLE USE AND MANAGEMENT OF AN IRRIGATION AREA IN THE SPANISH - PORTUGUESE BORDER THREATENED BY DESERTIFICATION - Muñoz, A (Desertification in the Mediterranean Region a Security Issue, 2006)
Inappropriate management of agricultural irrigated land, using excessive amounts of production factors – pesticides and fertilizers in particular – can lead to rapid and irreversible soil degradation and the corresponding decrease in production capacity. The method presented here, applicable to the entire Mediterranean region, was designed to support the sustainable management of a 12540 ha irrigated area located in the Spanish- Portuguese border, with special emphasis on the prevention of desertification. This specific tool, incorporates a data collection from 1428 georeferenced points and respective topsoil samples, describing soil type, depth, slope, drainage, pH, organic matter content, electrical conductivity, exchangeable sodium content, and available phosphorus and potassium. Parameterized maps were prepared for all these soil properties using Geographic Information System (GIS) software to store, manage, analyze, and display the georeferenced information. Predictive maps for organic amendments need were elaborated for use in the sustainable and integrated land management of the area. The higher risk zones were identified on the basis of their soil depth, slope, drainage, organic matter, electrical conductivity, and sodium saturation percentage.
Keywords: Caia Irrigation Perimeter; desertification; management (voyant); organic matter; soil properties